Democracy and power in alcohol premises licensing: A qualitative interview study of the Scottish public health objective. (11th June 2018) - Fitzgerald, Niamh; Winterbottom, Jo; Nicholls, James
Abstract: Introduction and Aims: There is international interest in how the availability of alcohol can be controlled to reduce harms. An objective of 'protecting and improving public health' was introduced to alcohol premises licensing in Scotland in 2005, resulting in public health actors engaging with licensing in new ways. We aimed to explore their experiences, including perceptions of the distribution of power, and constraints on their influence and that of the general public within the licensing system. Design and Methods: In‐depth, semi‐structured interviews were conducted with 13 public health actors who had recent and extensive experience of involvement in local licensing in 20 Scottish licensing jurisdictions. Interviews were audio‐recorded and analysed using an inductive framework approach. Results: Public health actors reported experiencing the licensing process as inherently unfair, with structures and traditions that were largely unhelpful to their efforts to support the public health objective. These included influence exerted by local officials, the formal and quasi‐judicial conduct of licensing meetings, and the disparity in resources available to public health actors versus licence applicants—with many larger applicants engaging specialist lawyers to represent their interests. The influence of public opinion—through, for instance, elected representatives' perceptions of public attitudes, consultation exercises and local 'licensing forums'—was seen as having a limited effect on decision‐making. Discussion and Conclusions: Changes to Scottish alcohol licensing ostensibly designed to enhance democratic engagement and promote public health, were as yet insufficient to change the system, or empower stakeholders, to fully achieve those goals.